Evaluation of Albumin 25% Use in Critically Ill Patients at a Tertiary Care Medical Center. (April 2020) - Torbic, Heather; Bauer, Seth R.; Militello, Michael; Welch, Sarah; Udeh, Chiedozie; Richardson, Steven
Background: Albumin 25% has been studied and has demonstrated benefit in a limited number of patient populations. The use of albumin 25% is associated with higher costs compared with crystalloid therapy. The aim of this study was to describe the prescribing practices of albumin 25% at a tertiary-care medical center and identify opportunities for restriction criteria related to its use to help generate cost savings.Methods: This evaluation was a retrospective, noninterventional, descriptive study of albumin 25% use between June 2015 and February 2016. Inclusion criteria consisted of patients ≥18 years old and who received at least one dose of albumin 25% while admitted to a Cleveland Clinic main campus intensive care unit (ICU). Inclusion was restricted to 150 randomly selected patients.Results: A total of 539 albumin 25% orders were placed for the 150 included patients. The cardiovascular ICU more frequently prescribed albumin 25% compared with the medical, surgical, neurosciences, and coronary ICUs (51% vs 23% vs 11% vs 9% vs 6%, respectively). Although the cardiovascular surgery ICU most frequently prescribed albumin 25% compared with other ICUs, the medical ICU prescribed a larger total quantity of albumin 25% compared with the cardiovascular, surgical, neurosciences, and coronary ICUs (8705 g vs 7275 g vs 3205 g vs 2162 g vs 625 g, respectively). The majority of patients (61%) did not have an indication listed for albumin 25% use and only 9% of patients were prescribed for indications supported by primary literature. Of the patients prescribed albumin for other indications not supported by primary literature (30%), the most common reasons for albumin 25% were hypotension, acute kidney injury, and volume resuscitation. The median cost per patient of albumin 25% was 417 with a total cost of 122 164 for the cohort. Only 19% of the total cost aligned with dosing regimens evaluated in primary literature.Conclusion: Prescribing patterns of albumin 25% at a tertiary academic medical center do not align with indications supported by primary literature. These findings identified a major opportunity for prescriber education and implementation of restriction criteria to target cost savings.